(untitled) (Palimpsesto, 2017)
This peace of paper describes the emergence of feminine figures through the action of woman in the press either directors, editors or producers of media. Considers two periods: 1850-1890 and 1900-1920. These feminine figures express an entrance strategy to Chilean intellectual field. They were taking place in the field until to be recognizing as intellectuals. These figures are: “The anonymous one who gave her opinion in politics”, “the publicist”, “The editor”, “the feminist worker”, “the politician”, “the feminist”, “the conservative”, “the feminist entrepreneur”, “the cultural entrepreneur”, “the literary editor”. The corpus is conformed by periodical papers produced by woman between 1850 and 1920.